Role-Playing Pedagogy for Disaster Mitigation Literacy among Child Hydrometeorological Hazard Survivors - Putri Khayriani; Syarfina Syarfina; Dedek Nursiti Khodijah (Journal of Education Research, 2026)
Indonesia's high vulnerability to hydrometeorological disasters highlights the inconsistent implementation of disaster mitigation education in early childhood settings. This study aimed to evaluate the effectiveness of structured role-playing in enhancing disaster preparedness among young children. A classroom action research study based on John Elliott's model was conducted with eight children aged 5–6 years at TAUD Luqmanul Hakim, Langsa, focusing on hazard identification, warning signs, and evacuation procedures. Data were collected through observation, performance rubrics, and field notes, then analyzed using descriptive percentages. Results demonstrated a significant improvement in student mastery, rising from 37% in Cycle I to 100% in Cycle II, categorized as "Very Good Progress." This outcome was driven by locally relevant scenarios and immersive multisensory media. These findings indicate that game-based pedagogy effectively transforms traumatic experiences into practical survival skills. Further research is recommended to examine psychological resilience and long-term skill retention across diverse high-risk zones.